Modelling flame turbulence interaction in RANS simulation of premixed turbulent combustion. Issue 1 (2nd January 2016) - Ahmed, Umair; Prosser, Robert
Abstract : Flame turbulence interaction is an important term for modelling scalar dissipation in premixed turbulent combustion. In order to obtain an accurate representation of the flame turbulence interaction phenomenon, an evolution equation for has recently been proposed. This equation gives a detailed insight into the flame turbulence interaction phenomenon and provides an alternative approach to modelling the important physics represented by . In this paper the evolution equation is used to model a premixed propane–air flame stabilised in a turbulent mixing layer. The simulations are carried out in the context of a Reynolds Averaged Navier–Stokes (RANS) framework and the results are compared with the experiments and also with Large Eddy Simulation (LES). It is found that the modelling strategy involving the evolution equation gives good approximations for the mean velocities and flame locations in the mixing layer stabilised flame when compared with other modelling strategies.